2016
DOI: 10.1017/s1049023x16000789
|View full text |Cite
|
Sign up to set email alerts
|

Case-based Learning Outperformed Simulation Exercises in Disaster Preparedness Education Among Nursing Trainees in India: A Randomized Controlled Trial

Abstract: Among nursing trainees assessed in this RCT, the CBL modality was superior to SEs in short-term disaster preparedness educational translation. Simulation exercises resulted in no detectable improvement in knowledge attainment in this population, suggesting that CBL may be utilized preferentially for adult learners in similar disaster training settings. Aluisio AR , Daniel P , Grock A , Freedman J , Singh A , Papanagnou D , Arquilla B . Case-based learning outperformed simulation exercises in disaster preparedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
1
20
0
3
Order By: Relevance
“…Harkrider et al () also reported that case‐based learning can readily improve knowledge. Aluisio et al () showed that nursing trainees’ knowledge improved through case‐based simulation training in disaster preparedness education. Taken together, these previous studies suggest that the acquisition of disaster nursing knowledge can be strengthened through the process of solving case problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harkrider et al () also reported that case‐based learning can readily improve knowledge. Aluisio et al () showed that nursing trainees’ knowledge improved through case‐based simulation training in disaster preparedness education. Taken together, these previous studies suggest that the acquisition of disaster nursing knowledge can be strengthened through the process of solving case problems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, case‐based learning has the advantage of using experiences that can be applied in real life while also demonstrating the learning contents (Yalçınkaya, Taştan‐Kırık, Boz, & Yıldıran, ). It is known to be effective in enhancing learners’ knowledge, attitude, and performance by inducing their active participation in learning (Aluisio et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…attitude, eventually improving clinical based thinking competency and skills of nursing interns [4,9]. This study also revealed that CBL could improve critical thinking ability of students, suggesting that CBL-method in combined with casedirected study significantly improved core competency of nursing undergraduates in solving clinical problems, and made them more competent for clinical practice in future [5].…”
Section: Application Of Case-based Learning In Instructing Clinical Smentioning
confidence: 60%
“…In practicing CBL, students are encouraged to perform prereading and discussion, followed by teacher-directed summary, thus developing systemic knowledge and skills from typical cases. As one open and interactive teaching method, CBL can maximally develop student's willingness for learning and creativity, activating student's mind and improving creativity idea, and guiding them to use gained knowledge to solve practical issues [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the knowledge of pathophysiology is solid or not is related to the study of clinical courses and gives proper diagnosis and treatment for diseases after graduation. Compared with the traditional teaching mode, case-based learning (CBL) focuses on more attention to how to systematically teach students the knowledge of pathophysiology, and cultivate students' ability to analyze and solve problems [3]. This paper introduced the CBL method into daily teaching in order to improve students' curiosity and interest in learning, so as to inspire students' creative thinking.…”
Section: Introductionmentioning
confidence: 99%